ANALYZING THE INFLUENCE OF VARIOUS FACTORS ON GENERATION Z'S BEAUTY PRODUCT PURCHASE BEHAVIOR - Natalie, Karen; Siregar, Bakti (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
In the digital era, Generation Z predominantly relies on digital platforms to select beauty products, both local and international, significantly impacting their purchasing decisions. This study investigates the influence of social media marketing, brand awareness, quality, price, online customer reviews, and discounts on Generation Z’s purchasing behaviours using multiple linear regression and correlation coefficients, analysed with R Studio and SPSS Statistics 25. A quantitative approach was employed, utilizing a questionnaire to collect data from 213 respondents. The results indicate that for international beauty products, social media marketing, brand awareness, product quality, and discounts are significant predictors of purchase intention (R² = 0.832). Conversely, for local beauty products, the key factors influencing purchase decisions are quality, price, online customer reviews, and discounts (R² = 0.790). These findings highlight that the determinants of Generation Z’s purchasing decisions vary based on the product type. While international products are more influenced by marketing and branding, local products are more affected by price and customer feedback. These insights are crucial for beauty brands aiming to tailor their marketing strategies effectively to engage Generation Z.